2004
DOI: 10.1029/2003ja010248
|View full text |Cite
|
Sign up to set email alerts
|

Generation of convective cells by kinetic Alfvén waves in the upper ionosphere

Abstract: [1] We consider the nonlinear interaction of finite amplitude kinetic Alfvén waves (KAW) with parametrically excited convective motions in the Earth's upper ionosphere, accounting for nonzero ion-Larmor radius effects. The generation of the convective cells is due to the Reynolds stresses of the Alfvén waves. These stresses are nonzero only when the perpendicular wavelengths of the kinetic Alfvén waves are of the order of the ionLarmor radius. It is found that the wave vector of the fastest growing convective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“…In some papers, a linear Boltzmann-like distribution of the ion density perturbation is used for obtaining closure [Onishchenko et al, 2004]:…”
Section: Nonlinear Eigenmode Equation For Kawsmentioning
confidence: 99%
See 1 more Smart Citation
“…In some papers, a linear Boltzmann-like distribution of the ion density perturbation is used for obtaining closure [Onishchenko et al, 2004]:…”
Section: Nonlinear Eigenmode Equation For Kawsmentioning
confidence: 99%
“…[8] KAWs are able to interact strongly with plasma species and with other wave modes, and hence they attract great interest [Hollweg, 1999;Stasiewicz et al, 2000;Voitenko and Goossens, 2003;Onishchenko et al, 2004]. The kinetic and inertial regimes of KAWs have been observed in the laboratory [Leneman et al, 1999;Kletzing et al, 2003] and in space [Leamon et al, 2000;Wygant et al, 2002;Chaston et al, 2003;Stasiewicz et al, 2004] plasmas.…”
Section: Introductionmentioning
confidence: 99%
“…The modulational instabilities correspond to four-wave interactions involving a pump KAW, a convective or magnetostatic cell, and two sideband KAWs. [6][7][8][9][10][11][20][21][22][23][24] In many laboratory and space plasmas, KAW turbulence instead of monochromatic KAWs are found. [25][26][27][28] Such turbulence can also drive lower frequency modes, in particular the zero-frequency CCs.…”
Section: Introductionmentioning
confidence: 98%
“…14 However, the dispersive shear or kinetic Alfvén waves (KAWs) [15][16][17][18][19] with perpendicular wavelengths of the order of the ion gyroradius, the ionacoustic gyroradius, or the electron inertial length can generate CCs. Theories have shown that modulational instability of the KAWs can excite electrostatic CCs in low-beta (b ( m e =m i ) plasmas and magnetostatic CCs in intermediatebeta (m e =m i ( b ( 1) plasmas, [6][7][8][9][10][11][20][21][22] where b is the ratio of the thermal to magnetic pressures and m e =m i is the electron to ion mass ratio. The modulational instabilities correspond to four-wave interactions involving a pump KAW, a convective or magnetostatic cell, and two sideband KAWs.…”
Section: Introductionmentioning
confidence: 99%
“…Both electron and ion nonlinear dynamics turn out to be essential for the nonlinear coupling, resulting in a jumplike transport of MHD wave energy directly in the dissipation range formed by KAWs. This nonlocal transport has several important advantages: it is not restricted to any specific wavelengths or frequencies of initial MHD Alfvén waves, and it does not require the preexistence of counterpropagating waves or plasma nonuniformities.Because of their ability to interact strongly with plasmas and with other wave modes, KAWs are now under intensive investigation [8][9][10][11][12]. The kinetic and inertial regimes of KAWs have been observed in the laboratory [13,14] and in space [3,[15][16][17] plasmas.…”
mentioning
confidence: 99%